Role of Ephedrine and Epinephrine in the Management of Hypotension after Sub-Arachnoid Block (SAB) in Caesarean Section (Journal of the Bangladesh Society of Anaesthesiologists, 2017)
Introduction: Caesarean section is a common operation in obstetrics and usually performed by subarachnoidblock (spinal anaesthesia). The principal advantages of spinal anaesthesia for caesarean deliveryare its simplicity, speed, reliability, & minimal foetal exposure to depressant drugs. The parturient remainsawake, & the hazards of aspiration are minimized.1Hypotension remains the most common complication associated with spinal anaesthesia for caesareandelivery. It can have detrimental effect on both mother & neonate ; these effects include impaired foetaloxygenation with asphyxial stress & foetal acidosis, & maternal symptoms of low cardiac output , suchas nausea, vomiting, dizziness, & impaired consciousness .2 Excessive hypotension may potentially producemyocardial and cerebral ischaemia, and is associated with neonatal acidaemia.3 Maternal hypotensionlasting more than 2 minutes should be avoided , as it may be associated with lower Apgar scores.1Hypotension after spinal anaesthesia for caesarean section has an incidence up to 80% without prophylacticmanagement.4 Recommended measures to decrease the incidence of hypotension include pre-hydrationwith 1000-1500 ml of lactated Ringer’s solution & maintaining left uterine displacement duringanaesthesia.1Despite these conservative measures, a vasopressor drug is often required. The drug usually recommendedin this context is ephedrine, which is effective in restoring maternal arterial pressure after hypotension.2Despite the wide acceptance of ephedrine as the vasopressor of choice for obstetric anaesthesia5, itssuperiority over other vasopressors has not been clearly defined and its position has been challengedbecause of potential complications that include supraventricular tachycardia, tachyphylaxis and foetalacidosis.6,7Moreover, when the fall of blood pressure is much greater, ephedrine does not exhibit prompt effect; inthat case, epinephrine would be the better option as a vasopressor agent in restoring maternal arterialpressure as because it is very quick on onset & very potent on action and does not exhibit tachyphylaxis.This study assesses whether the use of Ephedrine and Epinephrine are different in their efficacy formanaging maternal hypotension and their effects on neonatal outcome in women having spinal anaesthesiafor caesarean delivery.Summary: One hundred and sixty-seven (167) healthy patients, aged between 20 to 40 years, undergoingelective caesarean section under subarachnoid block (SAB) were assessed to determine maternalhaemodynamic changes and neonatal Apgar score. Among the 167 patients, sixty (60) patients developedhypotension; These 60 patients were divided into two groups.In Group A (n=26), Systolic blood pressure (SBP) decreased 83.56 (±4.84) mm Hg and Ephedrine wasgiven in 5 mg increments to maintain SBP > 90 mm Hg. Diastolic blood pressure (DBP) also reduced to61.26 (±4.94) mm Hg from its baseline value of 76.24 (±7.35) mm Hg and following Ephedrine therapy itrestored toward baseline value, 70.32 (±5.67). In Group B (n=27), Systolic blood pressure (SBP) decreased84.12 (±4.36) mm Hg and Epinephrine was given in 20 μgm increments to maintain SBP > 90 mm Hg.Diastolic blood pressure (DBP) also reduced to 62.19 (±4.78) mm Hg from its baseline value of 74.94(±7.05) mm Hg and following Epinephrine therapy it remained close to the value obtained duringhypotension, 63.06 (±3.59). Both the vasopressors restored the heart rate (HR) towards normal like 78.43(±7.35), & 82.85 (±5.68) from 108.24 (±8.45) & 109.34 (±11.04) beats/min, during hypotension by intravenousephedrine and epinephrine respectively.Conclusion: Use of Ephedrine and Epinephrine for the management of maternal hypotension doesn’taffect the neonatal outcome; neonatal Apgar score remains satisfactory. Epinephrine causes promptrestoration of systolic blood pressure towards baseline but doesn’t increase the diastolic blood pressure,thus may compromise the coronary perfusion. On the other hand, Ephedrine increases both systolic &diastolic blood pressure and to be used routinely for the management of hypotension during caesareansection under subarachnoid block.JBSA 2017; 30(2): 53-65